Pengaruh Kualitas Laporan Keuangan, Kapasitas Sumber Daya Manusia, dan Aksesibilitas terhadap Pemanfaatan Laporan Keuangan - Akhmad Priharjanto; Nina Andriana (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to examine the effect of financial statement quality, human resource capacity, and accessibility on the use of financial statements. This research is more focused on the use of financial statements by internal users, namely the management in order to carry out management tasks ranging from planning, implementation, and control. The study was conducted in Tangerang District Government in early 2020. This research is a quantitative study with statistical analysis. The data used are primary data obtained through questionnaires distributed to the Regional Work Unit in Tangerang Regency government. Respondents in this study were 39 work units. The research model uses multiple linear regression. The results of testing the hypothesis obtained as follows. The variable quality of financial statements has a positive and significant influence on the monitoring of financial statements as hypothesized. The human resource capacity variable also has a significant positive effect which accordance with the hypothesis formulated. However, the accessibility variable gives different results from the hypothesis. The test results show that the accessibility variable does not significantly influence the utilization of financial statements.